The Legal Conundrum in the Implementation of the Convention on the Rights of the Child in Nigeria - Ibrahim Danjuma; Karatu Afabwaje Joel (Faculty of Law, Sriwijaya University, Indonesia, 2021)
International law or treaty binds a state where such state signed, ratified acceded or domesticated same. In a monist State, ratification alone suffices for the international law or treaty to become binding whereas, in a dualist State, domestication as a condition must have complied. It is because of the peculiarities within various nations' legal systems (Monist or Dualist system). In 1989, The United Nations Convention on the Rights of the Child (UNCRC), an international human rights instrument came into force. Since its domestication as the Child Rights Act (CRA 2003) in Nigeria by the National Assembly, only about 24 States have enacted the law for onward enforcement. Nigeria is a nation which became independent in the year 1960 comprising now of 36 states and Abuja as its Federal Capital Territory all under the Federal Government. Since its domestication as the Child Rights Act (CRA 2003) in Nigeria by the National Assembly, many States have enacted the law for onward enforcement. However, few states are yet to comply and raise a question as to whether the said CRC has a binding force in all the States of the Federation. This study aims to examine the extent of how the UNCRC and CRA are being enforced in Nigeria. This study's research methodology is purely doctrinal, where library materials such as books, articles from journals, and online articles have been carefully selected and analyzed for this research. This paper recommends establishing a global agency or organ that should be saddled with the responsibility of ensuring full compliance and enforcement of international laws or treaties.